Performance enhancement of solar powered floating photovoltaic system using arduino approach - Nur Amirah Abdul Jamil; Siti Amely Jumaat; Suriana Salimin; Mohd Noor Abdullah; Ahmad Fateh Mohamad Nor (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper presents Performance Enhancement of Solar Powered Floating Photovoltaic System using Arduino Approach. In the project, an Arduino nano as a main controller of the system. The objective of this project to monitor performance of the voltage, current and power output respectively. Furthermore, the prototype of the research is testing in two conditions: on water surface and on a land area. Based on the results, the power of the photovoltaic on the water surface is increased compared on the land area. The conclusion for this project is it can generate electricity using floating photovoltaic and the same time to monitor output of the system.